All-cause and in-hospital mortality after aspirin use in patients hospitalized with COVID-19: a systematic review and meta-analysis. Issue 1 (29th October 2022) - Baral, Nischit; Mitchell, Joshua D; Savarapu, Pramod K; Akanbi, Maxwell; Acharya, Bandana; Kambalapalli, Soumya; Seri, Amith; Bashyal, Krishna P; Kunadi, Arvind; Ojha, Niranjan; Volgman, Annabelle Santos; Gupta, Tripti; et al.
Abstract: Background: With the results of the largest randomized controlled trial (RECOVERY) and the most extensive retrospective cohort study on coronavirus disease 2019 (COVID-19) recently published, we performed a meta-analysis on the association of aspirin with mortality of COVID-19. We aimed to investigate the role of aspirin in COVID-19 hospitalizations. Materials and Methods: We searched PubMed, EMBASE and Cochrane databases for studies from 1 January 2020 until 20 July 2022, that compared aspirin versus non-aspirin use in hospitalized COVID-19 patients. We excluded case reports, review articles and studies on non-hospitalized COVID-19 infections. We used the inverse variance method and random effects model to pool the individual studies. Results: Ten observational studies and one randomized controlled trial met the criteria for inclusion. There were 136 695 total patients, of which 27 168 were in the aspirin group and 109 527 were in the non-aspirin group. Aspirin use was associated with a 14% decrease in all-cause mortality compared with non-aspirin use in patients hospitalized with COVID-19 [relative risk (RR) 0.86, confidence interval (95% CI) 0.76–0.97; P = 0.002; I 2 =64%]. Among subgroups of studies reporting in-hospital mortality in COVID-19 hospitalizations, aspirin use was associated with a 16% decrease in in-hospital mortality compared with non-aspirin use (RR 0.84, 95% CI 0.71–0.99; P = 0.007; I 2 =64%). Conclusion: Our study shows that aspirin decreases in-hospital mortality in patients hospitalized with COVID-19. Further studies are needed to assess which COVID-19 patient populations benefit most, such as patients on aspirin for primary versus secondary prevention of atherosclerotic disease. In addition, significant bleeding also needs to be considered when assessing the risk–benefit of aspirin use.